The Effectiveness of Implementation Independent Learning Activity Unit Teaching Materials in Economics Subject - Al-Azizi, Zuraida Hafsa; Haryono, Agung (Unversitas Negeri Malang, 2020)
The Independent Learning Activity Unit as a learning instrument for students to achieve knowledge and skills competency in learning is an interesting topic for discussion. Independent Learning Activity Unit has a fundamental role in developing independent learning strategies and helping students achieve mastery learning. This research used a qualitative approach. Evaluative research was implemented to determine the level of effectivity, feasibility, and objectivity. The model used in this study is the Stake Model (Countenance) evaluation model developed by Robert Stake. There were three stages carried out in this study, namely; Antecedents (input), Transaction (process), Output (output). The results of the implementation of the Stake Model (Countenance) research stage showed that the use of Independent Learning Activity Unit in class X Social Studies SMA Negeri 1 Malang was going well.